Students engage in primary literature in molecular biology techniques using an online journal club format. Issue 6 (20th October 2020) - Oxford, Julia Thom; Jorcyk, Cheryl L.
Abstract: Campus closures in Spring 2020 required rapid transition to online course delivery. Fall 2020 has similar needs and expectations. The Advanced Topics in Molecular Biology Techniques course, designed for upper division undergraduate and graduate students, uses a "journal club" format. The journal club format includes practice‐based learning and provides student choice. Examples from graduate students effectively model the expectations using near‐peer instruction. Teaching in the time of COVID‐19 requires openness to new ideas and modifications to previous approaches. We were able to move the course online with little interruption.